Autobiographical study on the problems of a beginning teacher of English in developing writing skills of pupils - González Jiménez, Javier (Didáctica. Lengua y Literatura, 2017)
This paper presents an autobiographical self-study that, through the analysis of a Primary Education beginning teacher´s class diaries, delves into the knowledge of the practical problems and dilemmas that appear in developing the pupils’ writing skills. Based on the qualitative analysis of the reflections included in these personal documents, a narrative report has been written in order to better understand the beginning teacher´s cognitive process and actions during daily practice to develop literacy in a foreign language.